Identification of Differentially Expressed Non-coding RNA Networks With Potential Immunoregulatory Roles During Salmonella Enteritidis Infection in Ducks - Zhang, Yu; Dong, Xiaoqian; Hou, Lie; Cao, Zhengfeng; Zhu, Guoqiang; Vongsangnak, Wanwipa; Xu, Qi; Chen, Guohong (Frontiers in Veterinary Science, 2021)
Salmonella enterica serovar Enteritidis (S. Enteritidis) is a pathogen that can colonize the preovulatory follicles of poultry, thereby causing both reduced egg production and an elevated risk of foodborne salmonellosis in humans. Although a few studies have revealed S. Enteritidis preferentially invades the granulosa cell layer within these follicles, it can readily persist and proliferate through mechanisms that are not well understood. In this study, we characterized competing endogenous RNA (ceRNA) regulatory networks within duck granulosa cells following time-course of S. Enteritidis challenge. The 8108 long non-coding RNAs (lncRNAs), 1545 circular RNAs (circRNAs), 542 microRNAs (miRNAs), and 4137 mRNAs (fold change ≥ 2; P < 0.01) were differentially expressed during S. Enteritidis challenge. Also, eight mRNAs, eight lncRNAs and five circRNAs were selected and the consistent expression trend was found between qRT-PCR detection and RNA-seq. Moreover, the target genes of these differentially expressed ncRNAs (including lncRNAs, circRNAs and miRNAs) were predicted, and significantly enriched in the innate immune response and steroidogenesis pathways. Then, the colocalization and coexpression analyses were conducted to investigate relationships between ncRNAs and mRNAs. The 16 differentially expressed miRNAs targeting 60 differentially expressed mRNAs were identified in granulosa cells at 3 and 6 hour post-infection (hpi) and enriched in the MAPK, GnRH, cytokine-cytokine receptor interaction, Toll-like receptor, endocytosis, and oxidative phosphorylation signaling pathways. Additionally, underlying lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA ceRNA networks were then constructed to further understand their interaction during S. Enteritidis infection. Lnc_012227 and novel_circ_0004892 were identified as ceRNAs, which could compete with miR-let-7g-5p and thereby indirectly modulating map3k8 expression to control S. Enteritidis infection. Together, our data thus identified promising candidate ncRNAs responsible for regulating S. Enteritidis infection in the preovulatory follicles of ducks, offering new insights regarding the ovarian transmission of this pathogen.